Men hauling scow along shore of Windy Arm, Tagish Lake, Yukon Territory, 1898. - Hegg, Eric A., 1867-1948 (1898)
Caption on image: "Windy Arm N.W.T. copyright 1898" Same as Hegg 703. Original photograph by Eric A. Hegg 2147A; copied by Larss and Duclos